Patients’ Perception of Quality of Diabetes Care Received in Ibadan, Nigeria (2018)
evaluation of care for diabetes from patients' perspective an important indicator of measuring quality of health services and improving treatment approaches but data of the nature are scarce in Nigeria. The study therefore investigated Patients' Evaluation of the Quality of Diabetes care (PEQD) in Ibadan. This descriptive cross-sectional study recruited 384 diabetic patients from three hospitals where specialised services are offered in Ibadan. A semi-structured pre-tested questionnaire was used to collect data. A 42-point PEQD questionnaire scale was used to collect data and a score of >21 was rated as good Perceived Quality of Care (PQC). Data were analysed using descriptive statistics, chi-square test and logistic regression set at 5% level of statistical significance. Mean age of respondents was 62.5 + 10.8 years and mean diabetes duration was 8.4 + 7.6. Majority (58.3%) of the respondents didn't know the type of diabetes they had. Patients aged less than 60 years were less likely to PQC received as good (OR: 0.21; CI: 0.05 - 0.91) compared to those who were above 60 years. More than half (55.0%) of the respondents perceive quality of care as good. Patients' assessment of the quality of diabetes care received was perceived good. There is need to sustain current satisfactory services in diabetic care and institutionalize periodic survey patients' satisfaction to provide feedback for future quality improvement